Integrating unorganised waste reclaimers into formal recycling systems: the positive role of key brokers - Robertson, Chad (Graduate School of Business (GSB), 2023)
Waste reclaimers create a significant impact through their role in the recycling industry. Yet, the majority perform their role undignifiedly and with little or no support. Over the past few years, this impact has been researched, acknowledged and publicised by the government and private sector. As a result, the Waste Picker Integration Guideline for South Africa was developed to assist organisations working with waste reclaimers. However, these guidelines were mainly derived from case studies where waste reclaimers were more organised than most South African waste reclaimers and none based in the Western Cape. The difference in organisation, location and demographics is significant as it alters the process used to integrate waste reclaimers. This research sought to understand better the processes used to integrate unorganised waste reclaimers into formal recycling operations or projects in the Western Cape. The case studies were selected based on an existing integration process between a formal entity, either public or private, and an informal waste entity, a group of unorganised waste reclaimers. Five case study projects were chosen. The case study analysis resulted in a process model that highlighted the central finding, the role of the “key broker”, who can build trust among the waste reclaimers and successfully integrate unorganised waste reclaimers. The findings show characteristics to play such a role and how crucial such trust-building is because waste reclaimers have a deep-seated distrust of actors in the formal sector. This research contributes to prior work by exploring what makes such integration processes successful even in the absence of large associations or intermediating NGOs.